Influence of Brand Image on Consumer Purchase Intention of Apple Smartphone - Shah, Rupesh (Nepalese Journal of Management, 2025)
This study examines the influence of brand image on consumer purchase intention of Apple smartphone. Purchase intention is the dependent variable. The selected independent variables are brand equity, brand image, perceived product quality, brand loyalty and brand awareness. The primary sources of data are used to assess the opinions of respondents regarding the brand equity, brand image, perceived product quality, brand loyalty, brand awareness and purchase intention. The study is based on the primary data of 124 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of the influence of brand image on consumer purchase intention of Apple smartphone. The study showed a positive impact of perceived product quality on purchase intention. It indicates that higher the quality of product, higher would be the purchase intention. Similarly, the study showed a positive impact of brand image on purchase intension. It indicates that higher the brand image, higher would be the purchase intension. Likewise, the study showed a positive impact of brand awareness on purchase intension. It indicates that increase in brand awareness leads to increase in purchase intension. Further, the study showed a positive impact of brand loyalty on purchase intension. It indicates that loyalty of customers towards the brand leads to change the purchase intention. In addition, the study showed a positive impact of brand equity on purchase intension. It indicates that desirability of brand leads to change in the perception of consumers.